MATHEMATICAL REPRESENTATION OF STUDENTS IN SOLVING CURVED-SIDED SPACE PROBLEMS IN TERMS OF LINGUISTIC, LOGICAL MATHEMATICAL AND VISUAL SPATIAL INTELLIGENCE - Lepertery, Marselina E; Mataheru, Wilmintjie; Ayal, Carolina S (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
One of the abilities needed in learning mathematics is solving mathematical problems. In learning mathematics, mathematical representations are needed by students in the problem solving process. Students tend to use mathematical representations, but sometimes do not understand what they are doing. In general, mathematical representation is also very instrumental in improving mathematical competence. In addition to representation, students also have intelligence, including linguistic, logical mathematical and visual spatial intelligence. This research is a descriptive qualitative research that aims to describe completely the mathematical representations of class IX students of SMP N 38 Central Maluku in solving curved-sided space building problems (tubes and cones) in terms of linguistic, logical mathematical and visual spatial intelligence. The instruments in this research are multiple intelligence questionnaire, test questions and interview guidelines. The subjects in this study were selected based on the results of filling out the intelligence questionnaire. The subjects chosen were CS with linguistic intelligence, JPT with mathematical logical intelligence and SRP with visual spatial intelligence. The validity of the data is done by using triangulation method, which is done by comparing the results of filling out the questionnaire, the results of the student problem solving ability test and the results of the interview. The results of this study are in the form of a description of the mathematical representations of class IX students of SMP N 38 Central Maluku in solving curved side room problems for each stage of problem solving according to Polya's stages.